Effect of an Ayurveda Treatment Protocol in Managing Autism: A Case Study - Kalawana ,O.T.M.R.K.S.B.; Nirosha, J.A.; Rupasinghe, A.D.S.; Perera, M.K.M.P. (University of Colombo, 2024)
Autism spectrum disorder is characterized by difficulties with social interaction, communication, and atypical behavior patterns. According to the WHO, one in 100 children worldwide has autism. Management of autism spectrum disorder typically includes speech therapy, occupational therapy, and physical therapy. This study focused on the effect of an Ayurveda treatment protocol for autism. A four-year, three-month-old boy with a pre-diagnosis of autism was brought to the Balaroga Outpatient Department of Ayurveda National Hospital. He exhibited 2-3 single-word speech, communication disturbances, poor eye contact, and hyperactivity for 2 years. He was admitted for inpatient treatment. In the first week, the treatment included Trikatukadi kasaya (¼ Patha), Chandrakalka 1 Madata with Mahadalu anupana. Following this, 14 Anu thaila pratimarsha nasya treatments were started, followed by 10 sessions of Shirodhara and 10 Shiro basti treatments with Divyanganadi oil. The child also received Vacha choorna (1.25 g), Kaluduru-thippili leha, and Brahmi Mandukaparni kashaya (¼ Patha) continuously. Finally, Datri choorna (2.5 g) and 5 Matra basti treatments with 50 ml Narayana oil were administered. Progress was evaluated based on professional observations of the child’s signs and symptoms and the mother’s reports of the child’s progress. During the Nasya karma treatment, significant improvements in speech were observed, with the child learning 12-15 new words, beginning to read, and forming two-word sentences. Attention improved, and hyperactivity was gradually controlled. In autism, changes are in the brain. According to Ayurveda, the nose is considered the entryway to the head; thus, medicine adiministered through the nasal route reaches the brain, regulates functions, while removing morbid doshas. Further, the medicine used in this treatment has Agni deepana, Sroto shodhana, Medhya properties, which control disease by correcting Agni, Tridosha and enhancing Dhee, Druti, Smriti. This case study demonstrates the efficacy of Ayurveda treatment in managing Autism. Further studies with larger sample are necessary to scientifically validate these finding
Keywords: Autism; Nasya Karma; Anu Thaila; Balaroga